Subconscious Buzzer in Strengthening Audience’s Subject Reality Construction Through Social Media Platform Facebook - Ja'far Auzan Muzakki (Jurnal Ilmu Komunikasi Acta Diurna, 2020)
A very tangible proof of the large impact of social media as the development of communication technology is the buzzer, which is able to influence the subjective reality of users, one of the biggest social media, Facebook. The development of social media interactivity itself also affects how buzzers are created, that is, unconsciously (subconsciously) through social media metaphors. So that the subjective reality of the audience as an output that is influenced by the buzzer becomes stronger. Sampling from the population is done by convenience sampling and data analysis techniques using multilinear regression analysis. Data shows that Facebook's interactivity and social media metaphors influence a 38.9% of the subjective reality of Facebook users on the COVID-19 pandemic issue in Indonesia. Meanwhile, the dimensions of the near and far subjective reality which is a measurement of the construction of subjective reality also become stronger and in line with the interactivity and social metaphors received and done by Facebook social media users.